Stable continuous-wave lasing from discrete cesium lead bromide quantum dots embedded in a microcavity - Zhang, Hongbo (2023)
All-inorganic cesium lead bromide (CsPbBr3) quantum dots (QDs) with high photoluminescence (PL) quantum efficiency have been reported as ideal gain materials for high-performance lasers. Nevertheless, isolated CsPbBr3 QDs have not achieved lasing emission (LE) due to finite absorption cross-section. Here, we demonstrate continuous-wave lasing of isolated CsPbBr3 QDs embedded in a microcavity. Distributed Bragg reflectors (DBRs), together with isolated CsPbBr3 QDs in a polymer matrix, are introduced to construct a vertical-cavity surface-emitting laser (VCSEL), which exhibits stable single-mode lasing emissions with an ultra-low threshold of 8.8 W cm-2 and a high Q factor of 1787. Such perovskite-based microcavity structures sustain highly stable excitons at room temperature and can provide an excellent experimental platform to further study the single-particle nano-lasers and quantum physics frontiers such as exciton-polariton condensation, single-photon emission, and optical quantum communication.